Specifics of Asbestos Utilization in the Second Half of the 4th Millenium Bc in the Eastern Fennoscandia (on the materials of lithic workshop Fofanovo XIII) - Blyshko Dmitrii V.; Danilov Gleb K.; Zhul’nikov Aleksandr M.; Nedomolkina Nadezhda G.; Tarasov Alexey Yu. (Поволжская археология, 2023)
The authors analys the cultural phenomenon of asbestos ware in the forest zone of North-eastern Europe in the second half of the 4th millennium BC. The dynamic of this phenomenon is studied on the materials of the site Fofanovo XIII, which combines characteristics of metatuff adze and axe workshop, asbestos ware workshop, and interregional center for social communication. Typological and spatial analysis of the ware collections allows us to distinguish two periods of asbestos ware distribution in the late Neolithic-Eneolithic. During the first period (3500–3300 BC), asbestos ware (type Voinavolok) had high social status and was distributed far from the zone of natural deposits of this mineral. Distribution of asbestos ware at this stage fits the model of prestige economy. During the second period (3300–3100 BC), asbestos ware (type Orovnavolok) lost its interregional status. The distribution zone of the asbestos ware had decreased and took its place in linear economic connections. Statistical comparison of the metric parameters of pieces of asbestos collected on the site, as well as phase and chemical analysis show that changes in the social role of asbestos correlated with the downgrade of the mineral raw material quality, and increase of its variability. The authors suggest that this dynamic could be explained in the context of the change in the role of the social centers on the western shore of lake Onega, presented by site Fofanovo XIII.